STRATEGI MANAJEMEN PT. ASTRA MOTOR SUMBAWA DALAM MEMPERTAHANKAN EKSISTENSI PERUSAHAAN DI MASA PANDEMI COVID-19 - Elfa Dwi Utami; Elly Karmeli (Fakultas Ekonomi dan Manajemen, 2023)
This study aims to determine the management strategy of PT. Astra Motor Sumbawa in maintaining the existence of the company during the Covid-19 Pandemic. The type of data used is a qualitative obtained directly from primary sources through interviews. The research informants are all employees of PT. Astra Motor Sumbawa totaling 10 people. The data used in this study were obtained through the interview method and will then be analyzed using the SWOT analysis technique. Based on the results of the SWOT analysis of PT. Astra Motor Sumbawa in maintaining the company's existence during the Covid-19 Pandemic, the findings of researchers in the field refer to several strategies that can be implemented, namely: the S-O strategy is a strategy that uses strength by increasing employee productivity to take advantage of opportunities by using better digital transformation. The W-O strategy is a strategy that minimizes weaknesses by maintaining employee professionalism in satisfying consumers to take advantage of opportunities by maintaining consumer confidence in the production quality of Honda motorbikes. The S-T strategy is a strategy that uses strengths by optimizing good relations with consumers to overcome threats by increasing promotions in print and electronic media, and the W-T strategy is a strategy that minimizes weaknesses while maintaining the commitment of the company and partners in the sale of Honda motorbikes to avoid threats by monitoring activities competitor marketing.